Investigating the Relationship between Perceived Over-Qualification on Employee Career Performance: The Moderating role of Person-Organization Fit - Shafique, Ayesha (UW Journal of Management Sciences, 2023)
Purpose: In times of economic depression, over-qualification is frequent, and study has increasingly focused on its consequences. Based on the principle of person-job fit, the goal of this research is to examine the connection between perceived over-qualification and perceived career performance among employees, while analysing potential moderators. Despite the growing number of studies examining the association between perceived over-qualification (POQ) and perceived career satisfaction (PCS), the involvement of affective mechanisms in the relationship between POQ and PCS remains understudied. Design and Methodology: In this study, researchers focused on the impact of perceived organisation support (POS) as a mediator of the influence of perceived over-qualification (POQ) on perceived career performance (PCP) theorized by P-O fit theory. An analysis of 247 business sector subordinates conducted retrospectively provided support for the hypothesis by using SPSS 23. Findings: The current findings revealed that POQ showed significant relationship between PCS also mediate and moderate the relation. Implications: Theoretical and practical ramifications of these findings were analysed. Positive aspects of POQ and their impact on workers' professional lives were investigated in this study. Keywords: Perceived over-qualification, Perceived organizational support, Perceived career performance, P-O-Fit